Broadly inhibiting antineuraminidase monoclonal antibodies induced by trivalent influenza vaccine and H7N9 infection in humans - Rijal, P; Wang, BB; Tan, TK; Schimanski, L; Janesch, P; Dong, T; McCauley, JW; Daniels, RS; Townsend, AR; Huang, K-YA (American Society for Microbiology, 2020)
The majority of antibodies induced by influenza neuraminidase (NA), like those against hemagglutinin (HA), are relatively specific to viruses isolated within a limited time window, as seen in serological studies and the analysis of many murine monoclonal antibodies (MAbs). We report three broadly reactive human MAbs targeting N1 NA. Two were isolated from a young adult vaccinated with trivalent influenza vaccine (TIV), which inhibited N1 NA from viruses isolated from humans over a period of a hundred years. The third antibody, isolated from a child with acute mild H7N9 infection, inhibited both group 1 N1 and group 2 N9 NAs. In addition, the antibodies cross-inhibited the N1 NAs of highly pathogenic avian H5N1 influenza viruses. These antibodies are protective in prophylaxis against seasonal H1N1 viruses in mice. This study demonstrates that human antibodies to N1 NA with exceptional cross-reactivity can be recalled by vaccination and highlights the importance of standardizing the NA antigen in seasonal vaccines to offer optimal protection.